INVESTMENT FOR HIGHER EDUCATION IS THE INVESTMENT FOR FUTURE: Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
In an ever-evolving global landscape, the role of higher education in shaping the future cannot be overstated. This article explores the concept of investing in higher education as a strategic endeavor for securing future prosperity. It delves into the multifaceted benefits that accrue from such investments, ranging from individual career advancement to societal progress and economic growth. This article also covers 10 basic reasons why people should invest in their education and also tells about companies investing in their employees education.